ALIH KODE DALAM KANAL YOUTUBE GHIB OJISAN - Anggi Siska Hariyana; Anisa Arianingsih (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2021)
This study aims to determine the code switching function contained in the Ghib Ojisan YouTube channel video with the title Another 3 Things You Not Do To Japanese. The method used is descriptive qualitative method and data collection is fulfilled by transcription. The object of this research are sentences containing code switching in the video. The results of the study found in Ghib Ojisan's video entitled Another 3 Things You Should Not Do To Japanese are 4 functions such as message qualification, social routine, speech partner specification, and quotation. The most common function found is 5 data of message qualification, quotation is 2 data, while the least code-switching function is 1 data of the specification of speech partners and social routines.